Music As a Factor for The Formation of Social Identity in Youth - Mahmudova Sumbula Abdumalikovna (Zien Journals, 2022)
The study is of interest to music specialists, it allows a fresh look at the problem of teaching music for young people..
Keywords: Musical identification; musical preferences; musical identity; specialists